Radial porosity profiles are a powerful tool for tracing locomotor maturation in developing limb bones. (16th February 2023) - Prondvai, Edina; Butler, Richard J.
Abstract: Radial porosity profiles (RPP) are a new quantitative osteohistological parameter designed to capture the dynamic changes in the primary porosity of limb bones through ontogeny, providing insights into skeletal growth and functional development of extant and extinct vertebrates. Previous work hypothesized that RPP channelization—the intraskeletal alignment of RPPs across different bones resulting from similar cortical compaction patterns—indicates increasing locomotor performance of the developing limbs. By investigating RPPs in ontogenetic series of pheasants, pigeons and ducks representing distinct locomotor developmental strategies, we test this hypothesis here and show that RPPs are indeed powerful osteohistological correlates of locomotor ontogeny. Qualitative and quantitative analyses reveal strong association between RPP channelization and fledging, the most drastic locomotor transition in the life history of volant birds. The channelization signal is less clear in precocial leg function; however, when additional intraskeletal and intercohort RPP characteristics are considered, patterns related to leg precocity can also be identified. Thus, we demonstrate that RPPs can be used in future by palaeobiologists to generate breakthroughs in the study of the ontogeny and evolution of flight in fossil birds and pterosaurs. With further baseline data collection from modern terrestrial vertebrates, RPPs could also test hypotheses regarding ontogenetic postural shifts in dinosaurs and other terrestrial archosaurs. Abstract : Verifying on modern bird bones with differing developmental strategies, radial porosity profiles (RPP) are demonstrated to yield reliable information on locomotor ontogeny. RPP channelization is identified as the osteohistological correlate of functional maturation of the locomotor system, in particular related to fledging. RPPs can generate breakthroughs in studying ontogeny and evolution of flight in fossil birds and pterosaurs, and could also be used to test hypotheses regarding ontogenetic postural shifts in dinosaurs and other terrestrial archosaurs.